2010
DOI: 10.1002/app.31653
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermally conducting phase‐change materials based on polyethylene/wax blends filled with copper particles

Abstract: This article reports on the morphology, melting and crystallization behavior, thermal stability, tensile properties, and thermal conductivity of phasechange materials (PCM) for thermal energy storage. These materials were based on a soft Fischer-Tropsch paraffin wax (PCM) blended with low-density polyethylene, linear low-density polyethylene, and high-density polyethylene. These immiscible blends were melt-mixed with copper (Cu) microparticles (up to 15 vol %) to improve the thermal conductivity in the matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 24 publications
0
34
0
11
Order By: Relevance
“…Some of them [9,10] There are very few reports on the improvement of the thermal conductivity of polyethylene/PCM blend materials. Molefi et al [15][16][17] investigated the morphology, thermal and thermomechanical properties, as well as the thermal conductivities, of different polyethylenes mixed with different amounts of Fischer-Tropsch paraffin wax, as well as different amounts of copper micro-and nanoparticles. They found that the presence of the wax had the biggest influence on the mechanical properties of the phase-change composites, and that the wax preferably crystallized around the copper particles.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them [9,10] There are very few reports on the improvement of the thermal conductivity of polyethylene/PCM blend materials. Molefi et al [15][16][17] investigated the morphology, thermal and thermomechanical properties, as well as the thermal conductivities, of different polyethylenes mixed with different amounts of Fischer-Tropsch paraffin wax, as well as different amounts of copper micro-and nanoparticles. They found that the presence of the wax had the biggest influence on the mechanical properties of the phase-change composites, and that the wax preferably crystallized around the copper particles.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the thermal conductivity of the composites with increasing filler content was observed, as well as the formation of thermally conductive paths. However, one of the papers [12] reported an initial decrease in thermal conductivity at low filler contents, which increased at higher filler loadings. This was attributed to the voids that formed at the interface between the polymer and the wax.…”
mentioning
confidence: 99%
“…However, the presence of wood filler particles in the polymer/wax blends reduced the storage modulus [11]. The thermal conductivity of form-stable PCM composites was investigated in a number of studies [5,[12][13][14][15]. An increase in the thermal conductivity of the composites with increasing filler content was observed, as well as the formation of thermally conductive paths.…”
mentioning
confidence: 99%
“…Наночастицы меди распределяют в таких полимерах, как поливи-нилхлорид [38], полиэтилен [39,40], полипропилен [12,41,42], поли-стирол [43][44][45]. Важным требованием при синтезе таких композитных материалов является приобретение специфических свойств меди без утраты уже имеющихся свойств полимера (особенно прочностных па-раметров).…”
Section: методы распределения наночастиц меди в полимерахunclassified
“…Воск, внедренный в полимерную матрицу полиэтилена, применя-ется для хранения тепла солнечной энергии; тепловой защиты элек-тронных устройств, пищевых продуктов и изделий медицинского на-значения; снижения установленной мощности и теплового комфорта в транспортных средствах [40]. Такие характеристики материала до-стигаются за счет плавления и кристаллизации воска, в процессе кото-рых происходит накопление или высвобождение большого количества энергии.…”
Section: смесь полиэтилена и воскаunclassified